Analysis of structural, elastic and optoelectronic properties of indium-based halide perovskites InACl3 (A = Ge, Sn, Pb) using density functional theory. (1st November 2022) - Khan, Sajid; Mehmood, Nasir; Ahmad, Rashid; Kalsoom, Asma; Hameed, Khalid
Abstract: The structural, electronic, and optical properties of inorganic indium-based halide perovskites with new composition InACl3 (A = Ge, Sn, and Pb) are investigated in this work using density functional theory (DFT). These compounds are cubic in nature and their optimized lattice constants were found to be in the range 5.53–5.56 Å. The calculated band structure reveals that InGeCl3 has direct bandgap nature while InSnCl3 and InPbCl3 are having indirect bandgap. The energy band gap values are found to be 1.89 eV, 0.87 eV and 1.84 eV for InGeCl3, InSnCl3 and InPbCl3, respectively. This makes InGeCl3 an attractive option as a Pb-free material for photovoltaic applications. The semiconducting energy gaps of InSnCl3 and InPbCl3 show their suitability for solar cells. The elastic constants Cij are calculated and analyzed for studying the mechanical response of studied compounds to external forces. For the photons of 0–20 eV energy range, optical parameters such as the real and imaginary parts of the dielectric function, refractive index, reflectivity, and absorption coefficient are computed and discussed. The simulation results for the studied compounds are reported for the first time in the literature.